Enhancement the Performance of OFDM based on Multiwavelets Using Turbo Codes - Sameer A. Dawood; F. Malek; M. S. Anuar; HA Rahim (Universitas Ahmad Dahlan, 2015)
In wireless communication systems, the main challenge is to provide a high data rate and reliable transmission over a frequency selective fading channel. Orthogonal Frequency Division Multiplexing (OFDM) is a very attractive technique for high data rate transmission with better bandwidth efficiency. In this paper, the effectiveness of turbo codes is utilized to develop a new approach for an OFDM system based on a Discrete Multiwavelet Critical-Sampling Transform (OFDM-DMWCST). The use of turbo coding in an OFDM-DMWCST system is useful in providing the desired performance at higher data rates. Two types of turbo codes were used in this work, i.e., Parallel Concatenated Convolutional Codes (PCCCs) and Serial Concatenated Convolutional Codes (SCCCs). In both types, the decoding is performed by the iterative decoding algorithm based on the log-MAP (Maximum A Posteriori) algorithm. The simulationresults showed that, the turbo-coded OFDM-DMWCST system achieves large coding gain with lower Bit-Error-Rate (BER), therefore, offering a higher data rate under different channel conditions. In addition, thePCCCs offer better performance than SCCCs.